2020
DOI: 10.1101/2020.10.29.20207167
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Gastroenterological and Hepatic Manifestations of Patients with COVID-19, Prevalence, Mortality by Country, and Intensive Care Admission Rate: Systematic Review and Meta-analysis

Abstract: Background & Aims Patient infected with the SARS-COV2 usually report fever and respiratory symptoms. However, multiple gastrointestinal (GI) manifestations such as diarrhea and abdominal pain has been described. The aim of this study was to evaluate the prevalence of GI, liver function test (LFT) abnormalities, and mortality of COVID19 patients. Methods We performed a systematic review and meta-analysis of published studies that included cohort of patients infected with SARSCOV2 from December 1st, 20… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 97 publications
0
3
0
Order By: Relevance
“…COVID-19 pandemic, obesity and diabetes have been linked with a bad disease prognosis (17,59). Elevated levels of the liver enzymes AST/ALT (≥2× the upper limit of normal, i.e., 80 U/L]) are common, and are independently associated with adverse clinical outcomes among COVID-19 patients (60)(61)(62). In one study, AST/ALT elevations were observed in 235 patients classified as having severe COVID-19 (56).…”
Section: Accepted Articlementioning
confidence: 99%
See 1 more Smart Citation
“…COVID-19 pandemic, obesity and diabetes have been linked with a bad disease prognosis (17,59). Elevated levels of the liver enzymes AST/ALT (≥2× the upper limit of normal, i.e., 80 U/L]) are common, and are independently associated with adverse clinical outcomes among COVID-19 patients (60)(61)(62). In one study, AST/ALT elevations were observed in 235 patients classified as having severe COVID-19 (56).…”
Section: Accepted Articlementioning
confidence: 99%
“…(17,59) Elevated levels of the liver enzymes AST/ALT (≥2× the upper limit of normal [i.e., 80 U/L]) are common, and are independently associated with adverse clinical outcomes among patients with COVID-19. (60)(61)(62) In one study, AST/ALT elevations were observed in 235 patients classified as having severe COVID-19. (56) Another study included 31,461 adults with COVID-19, and found that moderate/severe liver disease was significantly associated with mortality (odds ratio [OR], 2.62; 95% confidence interval [CI], 1.53 to 4.47).…”
Section: Fatty Liver and Covid-progressionmentioning
confidence: 99%
“…However, some studies did not report such findings, and even the presence of gastrointestinal symptoms is associated with lower circulating cytokine levels, reduced disease severity, and reduced mortality (Dong et al, 2020;Tabesh et al, 2022). Two recent meta-analysis also suggested no difference in mortality between patients with and without gastrointestinal symptoms (Shehab et al, 2021;Wang et al, 2022). These results indicate that the role of gastrointestinal involvement in the course of COVID-19 requires further investigation.…”
Section: Discussionmentioning
confidence: 74%